Misclassification errors and the underestimation of the US unemployment rate - Shuaizhang Feng; Yingyao Hu (The Johns Hopkins University, Department of Economics, 2012)
Using recent results in the measurement error literature, we show that the official U.S. unemployment rate substantially underestimates the true level of unemployment, due to misclassification errors in the labor force status in the Current Population Survey. During the period from January 1996 to August 2011, the corrected monthly unemployment rates are between 1 and 4.4 percentage points (2.1 percentage points on average) higher than the official rates, and are more sensitive to changes in business cycles. The labor force participation rates, however, are not affected by this correction.
Keywords: J21; J64; C14; 330; Unemployment Rate; Labor Force Participation Rate; Misclassification; Measurement Error; Current Population Surveys